Contribution of free carriers to light absorption upon intense light-semiconductor interaction - Hollinger, Richard; Haddad, Elissa; Zapf, Maximilian; Shumakova, Valentina; Herrmann, Paul; Roeder, Robert; Uschmann, Ingo; Reisloehner, Udo; Pugzlys, Audrius; Baltuska, Andrius; Legare, Francois; Zuerch, Michael; et al. (2021 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2021, 2021)
In this work we investigated the role of free carriers in the interaction of a wide-band gap semiconductor with strong light fields at long wavelengths. Motivated by the beneficial scaling law of the pondermotive potential (U p Iλ 2 ), the interaction of intense long wavelength laser pulses with condensed matter has attracted huge attention over the last decade [Kruchinin]. After excitation of quasi free electrons in the conduction band (CB) via multiphoton absorption or tunnelling the strong pondermotive force leads to highly energetic free electrons. Bound electrons can be collisionally excited if the energy of the free electrons exceed the band gap energy. Here, we use the onset of near ultraviolet (NUV) stimulated emission in ZnO thin films ( Fig. 1a ) to study off-resonance light absorption and the role of free carriers thereby.
CRIS-Team Scopus Importer:2023-04-20